If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 = -7x + 6 Reorder the terms: -1 = 6 + -7x Solving -1 = 6 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. -1 + 7x = 6 + -7x + 7x Combine like terms: -7x + 7x = 0 -1 + 7x = 6 + 0 -1 + 7x = 6 Add '1' to each side of the equation. -1 + 1 + 7x = 6 + 1 Combine like terms: -1 + 1 = 0 0 + 7x = 6 + 1 7x = 6 + 1 Combine like terms: 6 + 1 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| 9/48/(-9/8) | | 2x+-2=4 | | (-3)(-5)(-4)(-10)= | | -1=-7x+6y | | y^2+y-0=0 | | x-246=688 | | -8(-4)= | | -7(-7)+6y=-42 | | -32-(-74)= | | 2/3(12x-15)+1/4(24x-16) | | 6k-13=4k+14 | | x/3+5=x/6+18 | | -32-16-(-27)= | | -4(-3a+6)+8(8a+7)=-44 | | 2+3x+5=25 | | 3x+2x+7=22 | | 2z^2+2z+13=0 | | (295.5-y)/5.5=x | | 3(8-7n)=-34+8n | | 295.50-y/5.5=x | | m-3=2 | | -56+38= | | -7*-7+6y=-42 | | 4a-8(-5-6a)=40-8a | | 11+3x-7=9 | | 106=-7(p-7)+1 | | -1=-10/9x+10 | | -1=-10/9+10 | | -16-5x=5-sx | | (4x-3)/5=(2x-7)/8 | | -1.1111=-10/9x+10 | | -1.1111=-10/9+10 |